1993
DOI: 10.2527/1993.7151226x
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of different types of clay for reducing the detrimental effects of aflatoxin-contaminated diets on performance and serum profiles of weanling pigs

Abstract: Three trials were conducted with recently weaned pigs (n = 198) to determine the effects of feeding different types of clay in conjunction with aflatoxin-contaminated diets. In Trial 1, pigs (n = 54; trial length 4 wk) were assigned to either an uncontaminated treatment (NC), 800 ppb of aflatoxin from contaminated corn (AC), or AC with one of four clays. In Trial 2 (n = 81; trial length 5 wk), pigs were assigned to NC, AC (500 ppb of aflatoxin from rice starch), or AC with one of seven types of clay. In both t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
70
0
6

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(88 citation statements)
references
References 7 publications
8
70
0
6
Order By: Relevance
“…Reduced mycotoxin absorption from the gastrointestinal tract has been shown to ameliorate its adverse effects on serum clinical chemistry of growing pigs (Scell et al, 1993) and broilers (Oguz et al, 2000). Representative feed samples were collected on a monthly basis and forwarded to BIOMIN Laboratories (BIOMIN Gesunde Tierernahrung International Gmbh, Herzogenburg, Austria) for the determination of aflatoxin B 1 concentration.…”
Section: Feeding Of the Animalsmentioning
confidence: 99%
“…Reduced mycotoxin absorption from the gastrointestinal tract has been shown to ameliorate its adverse effects on serum clinical chemistry of growing pigs (Scell et al, 1993) and broilers (Oguz et al, 2000). Representative feed samples were collected on a monthly basis and forwarded to BIOMIN Laboratories (BIOMIN Gesunde Tierernahrung International Gmbh, Herzogenburg, Austria) for the determination of aflatoxin B 1 concentration.…”
Section: Feeding Of the Animalsmentioning
confidence: 99%
“…The same authors (Schell et al, 1993b) found in another study with 0.5 % different clays (palygorskite, sepiolite, a treated Ca-bentonite (chemically and physically modified), hydrated sodium calcium aluminosilicate) and a diet with 800 µg AfB 1 /kg, that considerable differences between the clays exist. The modified Ca-bentonite restored pig performance and serum biochemistry to control levels.…”
Section: Pigsmentioning
confidence: 73%
“…This strategy has been the subject of considerable research in recent years. Various absorbing materials have been used including charcoal, zeolites, bentonite, spent bleaching clay from vegetable oil refining, and hydrated sodium calcium aluminosilicate (Schell et al 1993;Ramos & Hernandéz, 1997;Bailey et al 1998). The main problem is that mycotoxins are chemically quite diverse and so no single toxin-binding compound will be effective for all mycotoxins.…”
Section: Diet -Mycotoxin Interactionsmentioning
confidence: 99%